محتوى المنهاج التعليمي وعلاقته بالتحصيل الدراسي - جفال, جهاد (University of Eloued جامعة الوادي, 2021)
الملخص: هدفت هذه الدراسة إلى الكشف عن علاقة محتوى المنهاج التعليمي بالتحصيل الدراسي للتلميذ ولهذا العرض اعتمدنا التساؤل الرئيسي التالي:  ما علاقة محتوى المنهاج التعليمي بالتحصيل الدراسي للتلميذ؟ وقد تفرع عن هذا التساؤل مجموعة من التساؤلات الفرعية تمثلت في ما يلي: • ما علاقة كثافة محتوى المنهاج التعليمي بالتحصيل الدراسي للتلميذ؟ • ما علاقة صعوبة محتوى المنهاج التعليمي بالتحصيل الدراسي للتلميذ؟ وللإجابة على التساؤلات التالية قمنا بوضع فرضيات متمثلة في: • كثافة محتوى المنهاج التعليمي يؤدي إلى تدني مستوى التحصيل الدراسي للتلميذ. • صعوبة محتوى المنهاج التعليمي تؤدي إلى تدني مستوى التحصيل الدراسي للتلميذ. ولقد اقتضت طبيعة الدراسة إتباع المنهج الوصفي التحليلي الذي يعد من أكثر المناهج استخداما في العلوم الاجتماعية والإنسانية مع استخدام الاستمارة كأداة للحصول على المعطيات الميدانية، هذه الأخيرة التي طبقت على عينة الدراسة وقد احتوت على 28 بندا وتمثل مجتمع الدراسة في تلاميذ التعليم الثانوي وقدرت عينة الدراسة ب 113 تلميذا، وتوصلت الدراسة إلى النتائج التالية: • تحقق الفرضية الأولى: كثافة محتوى المنهاج التعليمي يؤدي إلى تدني مستوى التحصيل الدراسي للتلميذ. • تحقق الفرضية الثانية: صعوبة محتوى المنهاج التعليمي تؤدي إلى تدني مستوى التحصيل الدراسي للتلميذ. Résumé :فرنسية أو انجلزية This study aimed to reveal the relationship of the content of the educational curriculum to the student's academic achievement and for this presentation we adopted the following main question:  Whatdoes the content of the curriculum have to do with the student'sacademicachievement? A series of sub-questions have emergedfromthis question:: • Whatdoes the content density of the curriculum have to do with the student'sacademicachievement? • Whatdoes the difficulty of the curriculum content have to do with the student'sacademicachievement? To answer the following questions, wedevelopedhypotheses:: • The density of the content of the curriculum leads to a lowlevel of academicachievement of the pupil. • The difficulty of the content of the curriculum leads to a lowlevel of academicachievement of the pupil. The nature of the studyrequired to follow the descriptive and analytical curriculum, whichis one of the mostused curricula in the social sciences and humanitieswith the use of the form as a tool to obtainfield data, the latter applied to the sample of the study has contained 28 items and represents the studycommunity in secondaryeducationstudents and estimated: • Achieve the first hypothesis: the density of the content of the curriculum leads to a lowlevel of academicachievement of the pupil. • Achieve the second hypothesis: the difficulty of the content of the educational curriculum leads to a lowlevel of academicachievement of the pupil.
دراسة ميدانية بثانويتي: عيدة عبد الرزاق وعلي عون بولاية الوادي
مذكرة ماستر علم الاجتماع تخصص علم اجتماع التربية
Keywords: المنهاج التعليمي، التحصيل الدراسي; Programme d'études, réussite scolaire; Educational curriculum, academic achievement